Do wages compensate for anticipated working time restrictions? Evidence from seasonal employment in Austria - Emilia Del Bono; Andrea Maria Weber (Institute for the Study of Labor (IZA), 2006)
In this paper we investigate the existence of compensating wage differentials across seasonal and non seasonal jobs, which arise due to anticipated working time restrictions. We build on a theoretical model by Abowd and Ashenfelter (1981), which links the compensating wage differential to variation in individual unemployment through the effect of the unemployment insurance and the compensated labor supply elasticity. Since the Austrian labor market is characterized by an unusually high share of seasonal employment, our data provides the ideal setting in which to empirically test this model. We use the very rich information contained in the Austrian administrative records to derive a flexible definition of seasonal employment based on observed regularities in employment patterns. We find that employers pay on average a positive wage differential of about 11% for seasonal jobs and that the unemployment insurance system contributes a similar amount.
Keywords: J22; J3; C23; 330; seasonal employment; wage differentials; labor supply elasticity; fixed effects panel estimation; Lohn; Arbeitsrecht; Arbeitszeit; Saisonarbeitskräfte; Österreich